2003
DOI: 10.1038/sj.ejhg.5200965
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of nine chromosome probes in first polar bodies and metaphase II oocytes for the detection of aneuploidies

Abstract: We used fluorescent in situ hybridisation (FISH) to detect nine chromosomes (1,13,15,16,17,18,21,22 and X) in 89 first Polar Bodies (1PBs), from in vitro matured oocytes discarded from IVF cycles. In 54 1PBs, we also analysed the corresponding oocyte in metaphase II (MII) to confirm the results; the other 35 1PBs were analysed alone as when preimplantation genetic diagnosis using 1PB (PGD-1PB) is performed. The frequency of aneuploid oocytes found was 47.5%; if the risk of aneuploidy for 23 chromosomes is esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
1
4

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 70 publications
6
42
1
4
Order By: Relevance
“…Recently, in analysing the whole chromosome complement of MII oocytes and 1PBs by comparative genomic hybridisation (CGH) (Gutiérrez-Mateo et al 2004), a very similar frequency of aneuploidy was found (57.1%). Comparing the frequencies of aneuploidy for each of the analysed chromosomes (13, 16, 18, 21 and 22) obtained in the present work with those obtained for oocytes from normal karyotype females (Pujol et al 2003b), a slightly significant difference (PZ0.046) using the Chi-squared test was found.…”
Section: As In Reciprocal Translocationssupporting
confidence: 45%
“…Recently, in analysing the whole chromosome complement of MII oocytes and 1PBs by comparative genomic hybridisation (CGH) (Gutiérrez-Mateo et al 2004), a very similar frequency of aneuploidy was found (57.1%). Comparing the frequencies of aneuploidy for each of the analysed chromosomes (13, 16, 18, 21 and 22) obtained in the present work with those obtained for oocytes from normal karyotype females (Pujol et al 2003b), a slightly significant difference (PZ0.046) using the Chi-squared test was found.…”
Section: As In Reciprocal Translocationssupporting
confidence: 45%
“…The mechanism responsible for aneuploidies reported here had been previously described in 25.7% of the females when analysing MII-1PB doublets from IVM oocytes using 9-chr FISH. 5 The incidence observed in the present work is higher than the 13.2% found in IVF patients of 21-42 years of age [13][14][15] and in 22.6% of IVF oocytes from donorso29 years of age, 18 where the wholechromosome complement of mature oocytes (1PB-MII doublets) was evaluated.…”
Section: Segmental Imbalancescontrasting
confidence: 49%
“…4 An aneuploidy rate of 47.5% was observed when 1PB-MII oocyte doublets were analysed by 9-chr FISH. 5 In studies where the wholechromosome complement was assessed by spectral karyotyping, aneuploidy rates from 16.7% (10/60) 6 to 42.5% (20/47) 7 were detected. Using comparative genomic hybridisation (CGH), a great variability of aneuploidy rates was found, when different wholegenome amplification methodologies were used to amplify the DNA from single cells, and aneuploidy rates found in 1PB-MII oocyte doublets varied from 3% in oocyte donors 8 to 65% in IVF patients.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, chromosomes 13, 21, and X are involved in some of the most common human trisomies, and in the aneuploidies shown by oocytes at metaphase II (Cupisti et al 2003, Pujol et al 2003. In this paper, an extensive analysis of the pairing process and synapsis of homologues 13, 21, and X in 5876 oocytes is performed.…”
Section: Introductionmentioning
confidence: 99%